Predicting the cassava economy in Lampung province: An ARIMA-based forecast of supply, demand, and price - Zakaria, Wan Abbas; Tambunan, Varingan Prianando; Indriani, Yaktiworo (Edelweiss Applied Science and Technology, 2025)
Cassava productivity in Lampung Province experienced a decline from 2015 to 2019. This indicates that there are problems in cassava farming in Lampung Province. Apart from that, the tapioca industry in Lampung Province does not meet its need for fresh cassava as a raw material to produce around 9 million tons per year, so it can only produce around 7 million tons per year. This affects the price of cassava in Lampung Province. This research aims to predict the supply, demand, and price of cassava in Lampung Province, Indonesia. The utilized data type is secondary data with a time series of 14 years, from 2006 to 2019. The employed analytical technique is the forecasting method utilizing the ARIMA model. The research results obtained were that forecasting the supply of cassava in Lampung Province and forecasting demand for cassava for the gaplek industry and tapioca in Lampung Province experienced a decline in 2020-2025, while forecasting the price of cassava at the farmer level experienced an increase in 2020-2025. The government can anticipate this by investing in education, counseling, and infrastructure related to the cassava commodity, which currently provides very little outreach of counseling. Meanwhile, what the government can anticipate if there is a decline in cassava prices in the future is to increase the performance of cassava farmer groups so that they can sell their harvests collectively, giving farmers a higher bargaining power position in selling their production to industry.